(3QSGdI aj GdBOGH JMaI dHYV GdCMHGHs - (3Gdcahj, eMeO Hf MejO Hf eUWai, (B1174 (3g`s
(3ChdgG (B:s
(3MGeOG Gddg Ydi fYeGJg dNUJgG ef cJH gPG GdHGH JMaI dHYV GdCMHGH hJPcQI dChdj GdCdHGH ; GYde Cfc EPG bdJ HcdGe adc MGdGJ ; MGdI GdOYhi HdG Odjd hMGdI GdOYhi HGdOdjd hLGdI GdJYQja s
(3BNQgG (B:s
(3aGdfXQ aj GdHMK GdKGfj CjVG Ydi hLg GdSGHb Ke aj GdKGdK Ke aj GdQGHY hgcPG MJi JQJbj Edi eOGQL GdbHhd GdeDOhO GdMeO ddg Ydi GdJeGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\270s
(3EjVGM Gdecfhf (B1\3s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs